Activity and safety of the multi-target tyrosine kinase inhibitor cabozantinib in patients with metastatic gastrointestinal stromal tumour after treatment with imatinib and sunitinib: European Organisation for Research and Treatment of Cancer phase II trial 1317 'CaboGIST'. (July 2020) - Schöffski, Patrick; Mir, Olivier; Kasper, Bernd; Papai, Zsuzsanna; Blay, Jean-Yves; Italiano, Antoine; Benson, Charlotte; Kopeckova, Katerina; Ali, Nasim; Dileo, Palma; LeCesne, Axel; Menge, Franka; et al.
Abstract: Background: Gastrointestinal stromal tumour (GIST) is commonly treated with tyrosine kinase inhibitors (TKIs), but most patients ultimately develop secondary resistance. Cabozantinib, a multi-targeted TKI inhibitor, has activity in patient-derived GIST mouse xenograft models and can overcome compensatory MET signalling occurring on TKI treatment. European Organisation for Treatment of Cancer (EORTC) 1317 'CaboGIST' assessed the safety and activity of cabozantinib in patients with GIST who had progressed on imatinib and sunitinib. Methods: In this multi-center, open label, single arm phase II study, eligible GIST patients received oral cabozantinib (60 mg) once daily. Primary end-point was the progression-free survival rate at 12 weeks assessed by the local investigator per Response Evaluation Criteria in Solid Tumours 1·1. If at least 21 of the first 41 eligible and evaluable patients were progression-free at week 12, the activity of cabozantinib was sufficient to warrant further exploration according to the A'Hern one-stage study design. Findings: A total of 50 eligible patients started treatment between 02/2017 and 08/2018, including four (8%) still continuing cabozantinib at clinical cut-off (09/2019). The number of 3-weekly treatment cycles ranged from 1 to 30. Among the first 41 eligible and evaluable patients, 24 were progression-free at week 12 (58·5%, 95% confidence interval [CI] 42·0–74·0%). Among all 50 patients, 30 were progression-free at week 12 (60%, 95% CI 45–74%). Seven patients achieved a partial response (14%, 95% CI 6–27%), and 34 had stable disease (68%, 95% CI 53–80%) as best response. Progression was seen in eight patients (16%, 95% CI 7–29%), and one was not evaluable. Disease control was achieved in 41 patients (82%, 95% CI 69–91%). Median progression-free survival was 5·5 months (95% CI 3·6–6·9). The most common adverse events were diarrhoea (76%), palmar-plantar erythrodysesthesia syndrome (60%), fatigue (50%), hypertension (42%), weight loss (40%) and oral mucositis (30%), with 32 (64%) patients requiring dose reductions, 27 (54%) having treatment interruptions and no cabozantinib-related deaths observed. Interpretation: EORTC 1317 met its primary end-point, with 24/41 patients being progression-free at week 12 of treatment. The objective response was 14% with an encouraging disease control rate of 82%. Results of this trial confirm preclinical findings and warrant further exploration of cabozantinib in GIST. Clinical trial numbers: EORTC 1317, NCT02216578, EudraCT 2014-000501-13. Highlights: This is the first disease-specific trial of cabozantinib in the treatment of gastrointestinal stromal tumour. The primary end-point was met (24/41 of patients were progression-free at week 12). Cabozantinib provided clinical benefit (partial response + stable disease: 82·0%, 95% confidence interval [CI] 69·0–91·0%). The median overall survival was 18·2 months (95% CI 14·3–22·3). Cabozantinib provides encouraging disease control in patients who have progressed on imatinib and sunitinib.